The United States’ Withdrawal from the International Labor Organization - Beigbeder, Yves (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1979)
After a brief description of the I.L.O., this article summarizes the main events which led to the U.S. withdrawal, reviews precedents, then tries to explain the reasons for the U.S. withdrawal and lists its consequences.